Epistemic circularity and measurement validity in quantitative psychology: insights from Fechner’s psychophysics - Luchetti, Michele (Frontiers in Psychology, 2024)
The validity of psychological measurement is crucially connected to a peculiar form of epistemic circularity. This circularity can be a threat when there are no independent ways to assess whether a certain procedure is actually measuring the intended target of measurement. This paper focuses on how Fechner addressed the measurement circularity that emerged in his psychophysical research. First, I show that Fechner’s approach to the problem of circular measurement involved a core idealizing assumption of a shared human physiology. Second, I assess Fechner’s approach to this issue against the backdrop of his own epistemology of measurement and the measurement context of his time. Third, I claim that, from a coherentist and historically-situated perspective, Fechner’s quantification can be regarded as a first successful step of a longer-term quantification process. To conclude, I draw from these insights some general epistemological reflections that are relevant to current quantitative psychology.